STRATEGI PENDIDIKAN NILAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MI MATHOLIBUL HUDA JENGGOLO JENU TUBAN - Siti Nurjanah (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
The reality of children today tends to be far from positive values, family education is the first and foremost education in instilling values ​​to children, but school is a vital place that has an important role to introduce and instill values ​​to children so as to shape the character in the child. So this study aims to determine the value of education strategies in shaping the character of learners in MI Matholibul Huda jenggolo Jenu Tuban. This research is included in descriptive qualitative research which is intended to understand what phenomena experienced by research subjects. The results showed that the strategy of values ​​education in shaping the character of children is as follows first, exemplary strategy; second, advice (traditional); third, Knowing the good strategy; fourth, habituation strategy; fifth, the strategy of feeling and loving the good (feel good). While the impact of value education on the character of the child that includes: honest, discipline, responsibility, hard work, independent, creative, confident, religious, compassionate, appreciate Achievement, friendly / communicative, healthy lifestyle, courage, social care, and polite